SETTLEMENT OF REGION DISPUTES THROUGH THE CONSTITUTIONAL - Zuhdi Arman (eScience Humanity Journal, 2020)
Regional boundaries have an important meaning as the limits of regional government authority in carrying out regional government functions. Implies the emergence of conflicts between regions regarding the assertion of territorial boundaries because it is related to upholding the existence and sovereignty of each local government. In this research, the purpose of writing is not only to describe the conflict resolution process through the administrative process, but also relates to the settlement process through a review of the 1945 Constitution of the Republic of Indonesia by the Constitutional Court. The method used in this research is normative juridical. Through this research the writer can find research that is contrary to legal principles. Whereas Regulation of the Minister of Home Affairs Number 76 of 2012 is the correct regulation that is able to resolve conflicts in border areas. The administrative process regulated in Law Number 23 Year 2014 has not been able to resolve the problem of border area conflict even though the decision is a final decision but also has legal remedies as a review in court.